Ray [videorecording (Blu-Ray)] - Foxx, Jamie; Washington, Kerry, 1977-; Powell, Clifton; Ellis, Aunjanue; Lennix, Harry J.; Howard, Terrence; Tate, Larenz; King, Regina; White, James L.; Charles, Ray, 1930-2004 (Universal Studios Home Entertainment, 2011)
Dramatizes the life of Ray Charles, one of the founders of rhythm and blues music and one of the first African American recording artists to cross over to the pop charts, following events from his discovery of his talent to his struggles with drug addiction and rising success.